Activation of serum/glucocorticoid‐induced kinase 1 (SGK1) is important to maintain skeletal muscle homeostasis and prevent atrophy. Issue 1 (19th November 2012) - Andres‐Mateos, Eva; Brinkmeier, Heinrich; Burks, Tyesha N.; Mejias, Rebeca; Files, Daniel C.; Steinberger, Martin; Soleimani, Arshia; Marx, Ruth; Simmers, Jessica L.; Lin, Benjamin; Finanger Hedderick, Erika; Marr, Tom G.; et al.
Abstract: Maintaining skeletal muscle mass is essential for general health and prevention of disease progression in various neuromuscular conditions. Currently, no treatments are available to prevent progressive loss of muscle mass in any of these conditions. Hibernating mammals are protected from muscle atrophy despite prolonged periods of immobilization and starvation. Here, we describe a mechanism underlying muscle preservation and translate it to non‐hibernating mammals. Although Akt has an established role in skeletal muscle homeostasis, we find that serum‐ and glucocorticoid‐inducible kinase 1 (SGK1) regulates muscle mass maintenance via downregulation of proteolysis and autophagy as well as increased protein synthesis during hibernation. We demonstrate that SGK1 is critical for the maintenance of skeletal muscle homeostasis and function in non‐hibernating mammals in normal and atrophic conditions such as starvation and immobilization. Our results identify a novel therapeutic target to combat loss of skeletal muscle mass associated with muscle degeneration and atrophy. Abstract : Previous evidence suggests that Akt is the only determinant and regulator of cell survival in skeletal muscle. Here, the authors show that SGK1 is a novel and central factor mediating skeletal muscle preservation.